APLIKASI MASHLAHAT TRANSAKSI EKONOMI SYARIAH KONTEMPORER PADA MADRASAH ALIYAH JIDRIS SALAM PERSPEKTIF LEGISLASI - Ratno, Dedi (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2022)
This article describes the implementation of mursalah maslahat as an alternative source of lawIslam is related to transaction practices in the modern era that are increasingly flexible so that they canaccountable in sharia and can answer the challenges of the times. This researchusing qualitative methods and is a library research. Documentation data thatobtained from primary and secondary sources then reduced, verified and presented. ResultsThis research is: The perspective of the schools of jurisprudence, the pros and cons of the maslahah theory andthe comparison with qiyas, which turns out to only dwell in the realm of kaimat terms, becausein practice all schools use maslahah mursalah. Various forms of developmentIslamic economics, both institutional and product, shows that the role of maslahah mursalahvery significant. Like the trend of increasingly widespread Islamic banking, the emergence of Islamic credit cardswhich facilitates various transactions, updates in mudharabah transactions such as obligations,guarantee and profit sharing as profit sharing method. With the rapid development of Islamic economics,the use of maslahah mursalah will be more dominant and crucial so that Islamic law canadapt to every era and time